Factors influencing the research productivity of library and information science (LIS) faculty in higher education institutions an exploratory study - Carreon, Alec Andrei D. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
Library and Information Science (LIS) faculty members from five (5) higher education institutions (HEIs) in Metro Manila were surveyed to identify what factors affect their research productivity. These factors were divided into three (3) major characteristics namely, individual, institutional, and leadership. The Spearman's rho was used to determine the correlation of several factors with the LIS faculty research productivity.